Studies of native and exotic tree plantations in Sarawak - Vincent, Alexander (Universiti Malaysia Sarawak (UNIMAS), 2002)
Reforestation with indigenous tree species can play an important role in the restoration of unproductive degraded forestland resulting from shifting cultivation in Sarawak. To evaluate the mortality and growth of tree species planted in six different sites reforestation since 1984, demographic data from 100 plantation yield plots were analyzed and compared in this study. The seven species included in this study were Acacia mangium, Shorea macrophylla, Dryobalanops aromatica, S. parvifola, S. pinanga, S. splendida and Scaphium macropodum. Tree mortality and growth of A. mangium were size dependent in this study. Some indigenous tree species showed an encouraging growth rate. In the second part of this study, the performances of two of the above indigenous tree species (Dryobalanops aromatica and Shorea parvifolia) planted under different planting methods of establishment were analysed for mortality and growth.